Superior semicircular canal dehiscence postoperative outcomes: A case series of 156 repairs. (October 2019) - Romiyo, Prasanth; Duong, Courtney; Ng, Edwin; Wung, Vivian; Udawatta, Methma; Nguyen, Thien; Sheppard, John P.; Preet, Komal; Alemnew, Mahlet; Seo, David; Gopen, Quinton; Yang, Isaac
Highlights: 156 surgical repairs via middle fossa approach were performed at our institution. Resolution of SSCD symptoms may be dependent on gender. Bilateral SSCD was correlated with increased autophony post-surgically. Abstract: Previous studies have looked at differences in predisposing factors, symptomology, treatment options, and outcomes in patients with SSCD experiencing audiologic and vestibular symptoms, however this study utilizes data from the largest series of SSCD patients by a single pair of neurosurgeon and head and neck surgeon to date. The objective was to determine what pre-operative factors, if any, contribute to post-operative outcomes in SSCD patients. A retrospective chart review collected patient demographics, preoperative symptoms, and postoperative symptoms. Nonparametric tests were run using IBM® SPSS® Statistics. Fisher's Exact Tests, Spearman's rho, and McNemar's test for paired comparison of binary measures were performed, with a significance level of P < 0.05. A total of 156 SSCD surgeries were performed within a cohort of 119 patients. The majority of patients were female (n = 75, 63.0%). The median age was 55 years (±12.7 years) and median follow-up length was 0.46 months (range: 0.03–59.5 months). Increased postoperative dizziness and hearing loss was significantly correlated with females (P = .048, P = .041). Additionally, males reported significantly improved postoperative hearing (P = .044) with confirmatory audiometry. Serum ionized calcium levels inversely correlated with age using spearman's coefficient (rs  = −.260 P = .037). Postsurgical autophony was significantly associated with bilateral SSCD (P = .01). In conclusion, differences in outcomes between patients may have to do with bilateralism of SSCD or gender effects. Proposed theories concerning a "two hit" hypothesis and about calcium feedback regulation in SSCD may play a role in these findings. Understanding differences between symptomology will help facilitate discussions with future patients.